Development of an IoT-Controlled Automatic Air Fryer with Real-Time Monitoring via Blynk - Arya Sakti; Irma Salamah; Ali Nurdin (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2025)
The purpose of this study is to develop a prototype of an Internet of Things (IoT)-based automatic air fryer with a timer feature, which allows users to control and monitor the device remotely through the Blynk application. This system utilizes hot air circulation from heating elements and mechanical fans for the cooking process without using large amounts of oil. The methods used include hardware and software design, as well as testing the function of the ESP32-based control system. The main components in the system include a MAX6675 temperature sensor, an ESP32 microcontroller, a solid state relay (SSR), an MK2P relay, and the Blynk application as a user interface. The test results show that the system is able to automatically regulate the temperature and cooking time and provide a fast response via a Wi-Fi network. This study contributes to the development of an IoT-based control system for kitchen appliances, with a focus on the efficiency of remote control and monitoring. Evaluation of cooking quality is not the scope of this study and is recommended as an agenda for further study.